DETERMINANTS OF MURABAHAH FINANCING MEMBER DECISION FACTORS - Saputri, Mardini Indah; Irmayanti Hasan (I-Finance Journal, 2024)
This study aims to de determinants of murabahah financing member decision factors. This study uses an exploratory approach to explain the correlation between variables through hypothesis testing, with the research location at the BMT Cooperative Office of Sarana Usahawan Muslim Malang. The population in this study is members who use murabahah financing for buying and selling at the BMT Cooperative Sarana Wiraswasta Muslim Malang. Based on calculations using the Slovin formula, the number of samples in this study is 80 out of a total of 421 members who received business capital from the BMT Sarana Pengusaha Muslim Malang Cooperative using the purposive sampling technique. Primary data was obtained through surveys and interviews, as well as secondary data from the BMT Sarana Usahawan Muslim Cooperative. The data collection approach involves face-to-face interviews with questionnaires. Data analysis was carried out using SPSS, involving classical assumptions and hypothesis testing using t-test and F-test related to the influence of trust and company image on purchase decisions. The results of the study show that the company's trust and image have a positive and significant effect on the decision to purchase services with murabahah financing in the BMT Sarana Wiraswasta Muslim Cooperative, both partially and simultaneously.